2019
DOI: 10.1186/s12871-019-0888-2
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of renal function in cardiac surgery patients with low cardiac output syndrome: levosimendan vs beta agonists

Abstract: BackgroundSome studies have been performed to assess the effects of levosimendan on cardiac function when administered to cardiac surgery patients with low cardiac output syndrome (LCOS) in the immediate postoperative period. Levosimendan is an inotropic agent for the treatment of low cardiac output syndrome that seems to have a protective effect on renal function.MethodsIt is a quasi-experimental study. A total of 100 patients with LCOS received either beta-agonists or levosimendan. We assessed the incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In our study, the results also demonstrated that the incidence of renal insufficiency was significantly lower in the levosimendan group, which was consistent with the results of many studies that showed levosimendan can improve kidney function in cardiac surgery. Guerrero Orriach et al [ 26 ] demonstrated that the incidence of kidney failure was lower with the postoperative administration of levosimendan than with the administration of beta-agonists in patients undergoing cardiac surgery with LCOS. However, some studies have drawn different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results also demonstrated that the incidence of renal insufficiency was significantly lower in the levosimendan group, which was consistent with the results of many studies that showed levosimendan can improve kidney function in cardiac surgery. Guerrero Orriach et al [ 26 ] demonstrated that the incidence of kidney failure was lower with the postoperative administration of levosimendan than with the administration of beta-agonists in patients undergoing cardiac surgery with LCOS. However, some studies have drawn different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These aggregated findings are amplified by observations in a series of recent trials. Guerrero Orriach et al [ 79 ] have conducted a 3-year study in cardiac surgery patients with LCOS. A total of 100 adult patients meeting pre-specified criteria for LCOS requiring inotropic support were recruited, of whom 50 received levosimendan (0.1 μg/kg/min/24 h to a target dose of 12.5 mg) and 50 received unspecified beta-agonist inotropes at undisclosed dosages.…”
Section: In the Presence Of Renal Dysfunction/failurementioning
confidence: 99%
“…*Statistically significant difference. Figure drawn freely from the data reported by Guerrero-Orriach et al [ 79 ] …”
Section: In the Presence Of Renal Dysfunction/failurementioning
confidence: 99%
“…Cardiovascular response to levosimendan vs beta-agonists (such as dobutamine) in the treatment of LCOS has been assessed in a variety of studies ( Follath et al., 2002 ; Alvarez et al., 2013 ; Gandham et al., 2013 ; Xuan et al., 2013 ). The scientific literature demonstrates that levosimendan improves renal function, increases survival rates, and causes fewer side effects ( Yilmaz et al., 2007 ; Bragadottir et al., 2013 ; Yilmaz et al., 2013 ; Baysal et al., 2014 ; CHEETAH Study Group, 2018 ; Guerrero Orriach et al., 2019 ). Some studies suggest that the organ-protective effects of levosimendan are mediated by its action on potassium channels and mitochondria ( Kopustinskiene et al., 2004 ; Du Toit et al., 2008 ; Soeding et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%